Flexible Bronchoscopic Removal of Push-Pin from Right Lower Lobe Bronchus: a Case Report - Shrestha, Prajwol; Dhungana, Ashesh; Kayastha, Madhusudan; Shrestha, Manisha; Niroula, Deepa (Nepalese Medical Journal, 2020)
Foreign body aspiration is common in children and adolescents. Foreign body aspiration is often unnoticed and diagnosis may be delayed in children, as many fail to provide a history. Although rigid bronchoscopy is preferred modality, flexible bronchoscopy is also a useful tool for foreign body extraction from the distal airways in selected cases. An eleven-year-old boy presented with a history of fever and dry cough of one month's duration. A chest x-ray showed a linear radiopaque foreign body along the course of the right bronchus. Flexible bronchoscopy revealed a metallic nail-like structure in right lower lobe bronchus which was successfully grasped with the flexible forceps and extracted via the oral route with the bronchoscope. Upon extraction aspirated foreign body was found to be a push-pin.